Tracking carbon transfers embodied in Chinese municipalities' domestic and foreign trade. (10th August 2018) - Li, Y.L.; Chen, Bin; Han, M.Y.; Dunford, Michael; Liu, Weidong; Li, Zhi
Abstract: Cities are the major contributors to global carbon dioxide emissions; however, the carbon transfers embodied in cities' domestic and foreign trade have not been fully discussed. As carbon emissions from different domestic and foreign trade partners have not been distinguished, and since China's four municipalities (Beijing, Tianjin, Shanghai and Chongqing) carry an increasingly significant responsibility for carbon reduction in China, a multi-scale and multi-regional carbon emission assessment is applied to identify their emission transfers to and from 26 domestic provinces and 184 foreign economies. The results show that the intensities of the four municipalities are mainly above the international standard (0.14 kg/CNY) but beneath the Chinese average (0.24 kg/CNY). 71.72%, 55.35%, 65.34% and 33.65% of their emissions are imported from other regions. Generally, the four municipalities are net recipients of domestic carbon transfers and suppliers of foreign carbon transfers. Carbon transfers from Hebei to Beijing and Tianjin, Zhejiang to Shanghai, and Sichuan to Chongqing as well as from Beijing and Tianjin to Japan and South Korea and from Shanghai and Chongqing to the United States and Germany are identified in domestic and foreign supply chains. The multi-scale and multi-regional simulation and assessment in this work allows us to identify the carbon emissions not only within a city's boundaries but also via inter- and intra-national trade, providing a solid foundation for the carbon emission assessments of Chinese mega cities from an embodied perspective. Graphical abstract: Image 1 Highlights: Chinese municipalities' domestic and foreign carbon transfers are analyzed. Embodied carbon intensities and efficiencies of China's municipalities are assessed. Most municipalities are domestic recipients and global suppliers of embodied carbon. Municipalities' inter-national and intra-national carbon transfers are identified. Municipalities' responsibilities on alleviating environmental pressure are analyzed.